Analisis Putusan No. 1977/K.PID.SUS/2020 tentang Tindak Pidana Pencucian Uang - Stevanus, Rudolf; Rizki; Lombu, Ravid Aspin (DOKTRINA: JOURNAL OF LAW, 2025)
This study analyzes Supreme Court Decision No. 1977/K.PID.SUS/2020 concerning money laundering crimes. The study aims to evaluate legal considerations, the application of regulations, and their implications for preventing and combating money laundering in Indonesia. The research method used is normative legal research which refers to secondary data, data sources from literature and statutory regulations. The findings reveal that the application of Article 3 of Law No. 8 of 2010 in the decision aligns with the principles of legality, prudence, and justice. However, challenges such as limited human resources and technology hinder the effectiveness of law enforcement. Recommendations include enhancing training for law enforcement officials, harmonizing regulations, and strengthening financial activity monitoring